Global Bahadur representation for nonparametric censored regression quantiles and its applications - Efang Kong; Oliver Linton; Yingcun Xia (Centre for Microdata Methods and Practice (cemmap), 2011)
This paper is concerned with the nonparametric estimation of regression quantiles where the response variable is randomly censored. Using results on the strong uniform convergence of U-processes, we derive a global Bahadur representation for the weighted local polynomial estimators, which is sufficiently accurate for many further theoretical analyses including inference. We consider two applications in detail: estimation of the average derivative, and estimation of the component functions in additive quantile regression models.
Keywords: 330; Bahadur representation; Censored data; Kernel smoothing; Quantile regression; Semiparametric models; Nichtparametrisches Verfahren; Regression; Schätztheorie